2008
DOI: 10.1111/j.1439-0310.2008.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Learned Predator Recognition Mediated by Chemical Signals in Eurycea nana

Abstract: Effective and efficient predator recognition and avoidance are essential for the persistence of prey populations, especially in habitats where non‐native predators have been introduced. Predator recognition studies are commonly couched within a learned or innate dichotomous framework; however, characteristics of some systems or species could favor innate recognition combined with the ability to alter avoidance responses based on experience with predators. Eurycea nana is a fully aquatic salamander inhabiting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 55 publications
3
79
0
2
Order By: Relevance
“…These results substantiate other work that found that amphibians, including hellbenders, have innate behavioral responses to predator kairomones [32,59,60]. Crane and Mathis [11] found that larval hellbenders, 21-25 weeks old, increase their swimming when exposed to trout kairomones, which they interpreted as evidence of escape behavior.…”
Section: Discussionsupporting
confidence: 88%
“…These results substantiate other work that found that amphibians, including hellbenders, have innate behavioral responses to predator kairomones [32,59,60]. Crane and Mathis [11] found that larval hellbenders, 21-25 weeks old, increase their swimming when exposed to trout kairomones, which they interpreted as evidence of escape behavior.…”
Section: Discussionsupporting
confidence: 88%
“…The contextual behavioural response of agile frog larvae to dragonfly kairomone might thus be, to a large extent, innate (Lima and Dill, 1990;Scheurer et al, 2007;Epp and Gabor, 2008), as control tadpoles displayed the typical anti-predator behaviour upon their first postnatal experience with the odour of the predator (Fig. 2C,D).…”
Section: Discussionmentioning
confidence: 99%
“…These tests allowed us also to determine the effect of the site of origin (surface streams versus cave) and rearing conditions (predator and predator-free environments). Predator cues were obtained by maintaining six C. bidentata larvae for 24 h in 1.5 litres of dechlorinated tap water; the water was aliquoted (1 ml) and immediately stored at À20 C until use for behavioural tests, following the procedure of Epp and Gabor (2008). As control cues, we used 1 ml of tap water.…”
Section: Laboratory Experimentsmentioning
confidence: 99%